(untitled) (Perner’s Contacts, 2012)
The author deals with fleet management and it´s sub-system called “eco-driving”. Eco-driving is one of key sphere, in which enterprises still have possibilities to cut costs and to improve their entrepreneurship efficiency generally. The article is formed of presentation of development stages, main presumptions of realization and areas of fleet management´s application. Next, the article focuses on the usage of fleet management in road cargo transport range and the problem of eco-driving.